Organización contable al comercial “Ordoñez” de la parroquia Zumbi del cantón Centinela del Condor. Periodo del 01 de abril al 30 de junio del 2022. - Montero Vera, Karen Patricia (2023)
The title work called: ACCOUNTING ORGANIZATION TO THE COMMERCIAL "ORDOÑEZ" OF THE ZUMBI PARISH OF THE CENTINELA DEL CONDOR CANTON. PERIOD FROM APRIL 1 TO JUNE 30, 2022. It was carried out as a prerequisite to obtain the degree and title of Accounting and Auditing Engineer according with the Academic Regime Regulations of the National University of Loja in order to know the economic - financial situation and provide to the the owner with reliable and timely information through the Financial Statements as a basis for correct decision-making aimed for the growth and strengthening of this commercial company. According with the proposed objectives and for the fulfillment of them, the analysis of the basic data, line of business and the information provided by the owner of the Commercial "ORDOÑEZ" began, which served as a reference for the development of the chart accounts. duly codified in numerical and chronological form of all accounts in order to, serve as a basis for the application of accounting based on their own needs, politics and permanent control system of merchandise, accounts to which the respective description was made and the explanation of its movements according to its operations as a plan to guide its accounting; Subsequently, the Initial Inventory was carried out by reviewing the basic documentation that rests in the files and in this way to be able to verify and physically count the assets, values, rights and obligations of the commercial, which allowed determining its assets in $97,918.29, the liability at $39,635.56 and therefore an equity of $58,282.73, highlighting that the company, due to it is a commercial, has a value of $25,088.39 in merchandise. Also, the basic documentation was selected in an orderly and summarized way, on which auxiliary records were designed and in this form the appropriate transactions arising in the commercial were recorded through accounting entries in the journal, a process that afterwards led to the consolidation of the information both in the general ledger and trial 5 balance, which allowed the preparation of the Financial Statements, where the General Balance presents a total of assets of $107,384.98; liabilities $48,396.72 and equity of $58,988.26; while the Income Statement reflects income of $25,550.65 and expenses of $24,845.12, resulting in a profit for the year of $705.53; Similarly, the Cash Flow Statement reflects a balance of $26,166.59 for operating activities, which added to the initial balance, results in a final balance of $39,543.99, which is distributed in cash $502.56 and banks $39,041.43.